USING AUTHENTIC MATERIALS TO TEACH ENGLISH FOR COMPUTER NETWORK ENGINEERING STUDENTS IN BINA UTAMA VOCATIONAL HIGH SCHOOL, KENDAL - Susandari Susandari; I Gede Arga Anggara; Anisa Nur Azizah (Proceedings Education and Language International Conference, 2017)
In relation to the mission of the school, the graduate computer network engineering students of Bina Utama Vocational High School Kendal are expected to be educated competent labors who are digital literate and able to communicate in using foreign language. This quality standard graduate can be accomplished through the teaching English in the classroom. Furthermore, in the future, the graduate students will get additional benefit when they are certified and licensed in the field of computer network engineering that requires both vocational and English mastery. Hopefully, teacher can hold effective and proportional English learning process between theory and practice so that students can easily communicate using English as well as to compete with others from other countries in their future work especially to face ASEAN Economic Community Market. One way to create efficient English learning process is by bringing authentic materials in class. According to Wallace (1992:145) and Peacock (1997) in Berardo (2006), they describe authentic materials as real life materials which are not produced purposely to be used in the classroom but they can become the helpful learning material for students in completing some social purpose of the language community. The authentic materials are used in order to introduce English language in social context for the tenth grade students for recognizing some particular terms in the computer network engineering field. The results will show us the authentic based material which can be applied in syllabus of computer network engineering program especially in procedural text.Keywords: authentic material, syllabus, computer network engineering, vocational high school